Flex Behavior of Green SNFRC Circ Beams with Double-Layers of Spirals and Uniformly Distributed Reinf - Aswad, Nour Mohamad Ghazal (2021)
A Master of Science thesis in Civil Engineering by Nour Mohamad Ghazal Aswad entitled, “Flex Behavior of Green SNFRC Circ Beams with Double-Layers of Spirals and Uniformly Distributed Reinf”, submitted in December 2021. Thesis advisor is Dr. Mohammad AlHamaydeh. Soft copy is available (Thesis, Completion Certificate, Approval Signatures, and AUS Archives Consent Form).